2015
DOI: 10.1128/aem.01360-15
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Colitis by Lactobacillus casei BL23 Is Dependent on the Dairy Delivery Matrix

Abstract: The role of the food delivery matrix in probiotic performance in the intestine is not well understood. Because probiotics are often provided to consumers in dairy products, we investigated the contributions of milk to the health-benefiting performance of Lactobacillus casei BL23 in a dextran sulfate sodium (DSS)-induced murine model of ulcerative colitis. L. casei BL23 protected against the development of colitis when ingested in milk but not in a nutrient-free buffer simulating consumption as a nutritional su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 77 publications
0
64
0
Order By: Relevance
“…Totaled together, all these molecules will result in the overall health benefit expressed. The expression of those cell products also depends on the environmental context to which probiotics are exposed in prior to [50] or after [51] application. Nevertheless, this complexity of live microorganisms with their hundreds or thousands of probably bioactive molecules could be embraced to elucidate multi-factorial interactions between probiotics and their hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Totaled together, all these molecules will result in the overall health benefit expressed. The expression of those cell products also depends on the environmental context to which probiotics are exposed in prior to [50] or after [51] application. Nevertheless, this complexity of live microorganisms with their hundreds or thousands of probably bioactive molecules could be embraced to elucidate multi-factorial interactions between probiotics and their hosts.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies also support the anti-inflammatory activities of LTA from lactobacilli. L. casei BL23 had been shown to exert beneficial effects in the DSS-induced murine model of ulcerative colitis, and it was reported that the dltD mutant from the BL23 strain was unable to protect against the inflammatory damage induced by DSS (42).…”
Section: Discussionmentioning
confidence: 99%
“…The bacteria used are responsible for these anti‐inflammatory properties and at the same time assure fermentation, in contrast to probiotic dairy products available today which rely on different bacteria for fermentation and for immune modulation. Accordingly, L. casei BL23 was shown to attenuate mice colitis when provided in a fermented milk, yet not in a nutrient‐free buffer . Thus, the designed/tailored functional fermented dairy product is more than a food probiotic carrier .…”
Section: Discussionmentioning
confidence: 99%